The Correlation between Students’ Grammar Mastery and Writing Ability in Recount Text : English - Ukhtul Iffah; Nuril Firdaus; Ummi Fariqoh (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
The purpose of the study was to determine the relationship between eighth-grade SMP IT Fatwa Curah Kalak students' writing proficiency in recount texts and their command of grammar. The correlation method was used by the researcher. One class was used to conduct the study. There are 74 participants in this study, ranging from the first to the last class. Purposive sampling was employed to choose the twenty-four eighth grade pupils from SMP IT Fatwa as the study's sample. A grammatical mastery test was administered to the class following a teaching and learning program. The researcher administered a writing ability test consisting of 35 questions and 60 minutes. The focus of the writing test was on students recounting memorable experiences from the past into well-written pieces.The correlation value was determined using the Pearson algorithm in IBM SPSS Statistics version 22, and the correlation coefficient (r), which falls between 0.40-0.60, was found to be 0.526. It was found that there was a moderate amount of linkage. Nonetheless, in terms of relevance, the r-obtained compared with the critical value. It shown that the r-obtained value exceeds the r-critical value of 0.526 > 0.404 at the 0.05 significance level.